Vestiges de collections - Margaux Dumas (Les Cahiers de l'École du Louvre)
Moments of spoliation and restitution can be seen as passages in the life of objects that categorise them, make them part of our heritage, give them or take away their value, and document them. The Nazis’ vast undertaking of artistic predation was thus a major moment in the movement and loss of objects in Europe, particularly from private collections. Through the archives of the Commission de Récupération Artistique from 1944 to the 1950s, and by delving into Le Répertoire des biens spoliés published beginning in 1947, historians can bring to life rare objects, private collections, and dismantled and disappeared sets, recounting their respective biographies and offering a perspective on the tastes of the time, thanks to the descriptions, photographs and drawings that accompany the inventories. Le Répertoire des biens spoliés, sometimes the only documentation of seized works or collections, helped preserve cultural heritage as well as its memory. While the objects, through their materiality and presence, may then be considered witnesses to the past, their absence also constitutes a testimony of sorts.